Bacterial communities related to 3-nitro-1-propionic acid degradation in the rumen of grazing ruminants in the Qinghai-Tibetan Plateau. (December 2018) - Guo, Wei; Bi, Sisi; Kang, Jingpeng; Zhang, Ying; Long, Ruijun; Huang, Xiaodan; Shan, M.N.; Anderson, Robin C.
Abstract: The objectives of this current study were to characterize the overall rumen bacterial community in grazing yak and two sheep species (Tibetan and Small Tail Han sheep) reared in the unique environmental conditions of the Qinghai-Tibetan Plateau, as well as the bacterial community associated with the detoxification of a phytotoxin, 3-nitro-1-propionic acid (NPA), during in vitro culture with 4.2 mM NPA. Using 16S rRNA gene high-throughput sequencing, it was found that the yak rumen harbored populations showing a higher bacterial diversity compared to Tibetan sheep. The rumen bacterial community in the three ruminant species differed from each other. PICRUSt analysis identified that the pathway involved in nitrogen metabolism was enriched in Tibetan sheep while that related to fatty acid biosynthesis was over-represented in the yak. The methane metabolism pathway was dominant in bacterial populations from the Small Tail Han sheep. Comparisons between freshly collected rumen fluid and populations subjected to consecutive 72 h batch cultures revealed substantial decreases in alpha diversity in populations cultured with NPA. Moreover, the relative abundances of some bacterial taxa changed significantly, with increased abundance of Proteobacteria and Actinobacteria. In addition, the overall community structure of the bacterial population in the freshly collected ruminal fluid was clearly different than that within populations observed in the 72 h batch cultures likely due to the impact of NPA treatments and the more restrictive growth conditions of the culture medium. In regard to PICRUSt analysis, the methane metabolism pathway became scarce in Tibetan and Small Tail Han sheep, whereas the energy and carbohydrate metabolic pathways such as nitrogen metabolism, ABC transporters and glycolysis/gluconeogenesis were found to be maintained across all populations. Results from the present study provide new information on the bacterial and functional composition within ruminal populations adapted to three economically important grazing ruminant species prominent on the Qinghai-Tibetan Plateau. The results further reveal that effects of NPA treatment on community structure can have an impact not only the metabolism of NPA but on other digestive functions as well. Highlights: 3-Nitro-1-propionate degradation by Qinghai-Tibetan Plateau ruminants was explored. Ruminal communities from Yak, Tibetan and Small Tail Han sheep were investigated. Bacterial communities associated with NPA degradation were characterized.